Dynamic thermal analysis and 3E evaluation of a CCHP system integrated with PVT to provide dynamic loads of a typical building in a hot-dry climate. (August 2022) - Nikbakht Naserabad, Sadegh; Rafee, Roohollah; Saedodin, Seyfolah; Ahmadi, Pouria
Abstract: In this research paper, a combined heating, cooling and power (CCHP) generation system is integrated with PVT panels to meet the demand of an educational building. Hourly building loads, including heating, cooling, and electrical loads, are calculated dynamically. A MATLAB code was developed for techno-economic optimization of the system based on a one-year operation. The dynamic performance of a hybrid solar PVT system with MGT is included in the simulation. The possibility of buying and selling electricity with the network has also been considered in the optimization process. The results show a 30% drops in gas turbine power in the summer, while PVT power reaches a maximum of 30 kW in the warmer months of a year. The total electricity sold to the grid per year is 1.198MWh, which means the high economic value of the system for the building. The results also show that the system has the highest and lowest efficiency in July and January. The exergy efficiency in these two months is 46.67% and 19.33%, respectively. If the economic objective function is considered as the main priority for the design and one-year operation of the integrated system, the unit cost of production will be reduced to 12.27$/GJ.